A preparation method of surface-modified spherical silicon dioxide powder

By preparing spherical silica powder in flame method and hydrolyzing and coupling treatment, the SiOH content is increased, and the interfacial compatibility and binding force problems in its application in the semiconductor industry are solved, achieving better modification effects and Performance improvement.

CN115612315BActive Publication Date: 2024-12-24JIANGSU NOVORAY NEW MATERIAL CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202211516216.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2024-12-24
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

During the flame preparation process, the existing spherical silica micropowder is acidic due to adsorption of CO2, which affects the interface compatibility and binding force with organic resins. The SiOH content is insufficient, making it difficult to form a strengthened bond, which limits the application in the semiconductor industry. .

Method used

After the spherical silica micropowder is prepared by flame method, the hydrolysis reaction is carried out by adding alkaline substances and silicone sources to a mixed solution of pure water and ethanol or methanol to increase the SiOH content, and the residue is removed at high temperature, and then the use of the The coupling agent is modified to form more SiOH on the surface of the spherical silica micropowder, achieving neutral pH.

Benefits of technology

The surface modification effect of spherical silica micropowder is improved, the binding ability with resin is enhanced, and the application performance in the semiconductor industry is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE001
    Figure DEST_PATH_IMAGE001
Patent Text Reader

Abstract

The invention discloses a preparation method of surface-modified spherical silica micropowder. The method selects spherical silica micropowder produced by a flame method, wherein the median particle size of the spherical silica micropowder is 10nm-100μm, the pH value is 3.0-5.5, and the SiOH content is 1μg / g-3000μg / g. The method comprises the following steps: adding the spherical silica micropowder to a mixed solution of pure water and ethanol or methanol, then adding an alkaline substance to adjust the pH value of the solution to 7-9, stirring evenly, then adding an organic silicon source, reacting at a reaction temperature of 25-80°C for 0.5-12h, filtering, washing, and drying after the reaction, and then modifying the obtained spherical silica with a coupling agent to obtain a modified product. The present invention uses nano-silicon dioxide produced by hydrolysis and heat treatment of an organic silicon source to coat the surface of spherical silicon dioxide, thereby increasing the SiOH content on the surface and making the surface pH neutral, which is beneficial to the subsequent modification steps. The prepared modified product has better bonding ability with the resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to spherical silicon dioxide micropowder, and in particular to a preparation method of surface-modified spherical silicon dioxide micropowder. Background Art

[0002] Spherical silica powder has excellent heat resistance, weather resistance, chemical corrosion resistance, small CTE and comparable to semiconductor silicon data. It is widely used in the semiconductor industry, including semiconductor packaging, substrates, structural adhesives and other fillers. However, these organic resins and inorganic fillers have problems with interface compatibility and bonding strength. To solve these problems, measures for surface modification of fillers are proposed.

[0003] The spherical silica powder prepared by the flame method is obtained by the combustion of hydrocarbon-containing hydrocarbons. The SiOH content on the product surface is relatively low. Due to the adsorption of a small amount of combustion product CO2, the product is acidic, which causes a certain degree of solidification in acid-sensitive organic systems, affecting its application in the semiconductor industry.

[0004] Hydrocarbon-containing hydrocarbons are used as fuel to provide the high temperature required for the spheroidization of flame-processed fillers. A small amount of combustion product CO2 will be adsorbed on the surface of the product, and the product is acidic, which seriously limits its application in the semiconductor industry. In addition, after the high-temperature spheroidization process, the SiOH content on the surface of the spherical silica powder is relatively low, and it is not easy to react with the hydrolyzed SiOH in the coupling agent, and it is difficult to form a strong chemical bond, making it difficult to achieve effective interface bonding in subsequent use in specific systems.

[0005] The prior art also discloses a method of preparing a highly hydrophobic modified product by in-situ modification, which is patented in CN110372913A. This method is suitable for batch production of a single specification, and the coupling agents used are limited to a few coupling agents, so it is not possible to produce a small amount of special products, and the versatility and compatibility are poor. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a preparation method of surface-modified spherical silica powder with reasonable design, neutral pH of aqueous solution and excellent surface modification in view of the deficiencies of the prior art.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing surface-modified spherical silica powder, characterized in that the method uses spherical silica powder produced by a flame method, the median particle size of the spherical silica powder is 10nm-100μm, pH=3.0-5.5, and SiOH content is 1μg / g-3000μg / g. The method comprises the following steps:

[0009] (1) Add spherical silica powder to a mixed solution of pure water and ethanol or methanol, then add an alkaline substance to adjust the pH of the solution to 7-9, stir evenly, then add an organic silicon source, and react at a reaction temperature of 25-80°C for 0.5-12h. After the reaction is completed, vacuum filtration is performed to obtain a filter residue, and then the filter residue is washed with the above-mentioned mixed solution of pure water and ethanol or methanol in turn, and the washing is repeated three times, and then dried;

[0010] (2) The dried filter residue is treated in a calcining furnace at 300-800°C for 0.5-30h to remove a small amount of residual organic matter and alkaline substances, so that the hydroxyl content of silicon dioxide formed on the surface of the spherical silicon dioxide powder is more prominent;

[0011] (3) The surface of spherical silica is coated with high-purity silicon oxide formed by hydrolyzed organic silane, and a larger SiOH is formed on its surface. The pH of the aqueous solution is neutral, and then it is modified with a coupling agent to obtain a modified product. The median particle size of the spherical silica powder after surface modification is 10nm~100μm, pH=5.5~7.5, and SiOH content is 1μg / g~2000μg / g.

[0012] The technical problem to be solved by the present invention can also be achieved by the following technical solution, wherein the weight ratio of the spherical silicon dioxide powder: a mixed solution of pure water and ethanol or methanol: an organic silicon source is 100:1000:0.01-10.

[0013] The technical problem to be solved by the present invention can also be achieved by the following technical solution, wherein the mass ratio of pure water to ethanol or methanol in step (1) is 100-1:1.

[0014] The technical problem to be solved by the present invention can also be achieved by the following technical scheme: step (1), taking 100 parts of spherical silica powder and adding it to a mixed solution of 1000 parts of pure water and ethanol or methanol, then adding an alkaline substance to adjust the pH of the solution to 7-9, stirring evenly, and then adding 0.01-10 parts of an organic silicon source; the reaction temperature is 25-80°C, the reaction time is 0.5-12h, after the reaction is completed, vacuum filtration is used, the filter residue is washed with pure water and an alcohol mixture in turn, and the washing is repeated three times, and then drying is performed, and the drying condition is drying at 100°C to 200°C for 1h to 12h.

[0015] The technical problem to be solved by the present invention can also be achieved by the following technical scheme, wherein the alkaline substance is selected from one or more of triethylamine, ammonia water, pyridine, tetramethylethylenediamine, hexamethyldisilazane, aminopropyltriethoxysilane, methylamine, urea, dimethylamine, and aniline.

[0016] The technical problem to be solved by the present invention can also be achieved by the following technical solution, wherein the organic silicon source is selected from at least one of methyl orthosilicate, ethyl orthosilicate, γ-(methacryloyloxy)propyltrimethoxysilane, butyltrimethoxysilane and methyltriethoxysilane.

[0017] The technical problem to be solved by the present invention can also be achieved by the following technical solution: the coupling agent is Si(R 1 ) X (OR 2 ) 4-X , X can be 1, 2 or 3, R 1 is a hydrocarbon group containing an alkyl group, an epoxy group, a hydroxyl group, an amino group, a carboxyl group, a mercapto group, an isocyanate group, an ethoxy group, or a urea group, and R 2 It is methyl or ethyl.

[0018] Compared with the prior art, the present invention uses nano-silica produced by hydrolysis and heat treatment of an organic silicon source to coat the surface of spherical silica, thereby increasing the SiOH content on its surface and making the surface pH neutral, which is beneficial to the subsequent modification steps. The prepared modified product has better bonding ability with the resin. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0020] A method for preparing surface-modified spherical silica powder, wherein the method uses spherical silica powder produced by a flame method, wherein the median particle size of the spherical silica powder is 10 nm-100 μm, the pH value is 3.0-5.5, and the SiOH content is 1 μg / g-3000 μg / g. The method comprises the following steps:

[0021] (1) Take 100 parts of spherical silica powder and 1000 parts of a mixed solution of pure water and ethanol or methanol, the mass ratio of pure water to ethanol or methanol is 100-1:1, then add an alkaline substance to adjust the pH of the solution to 7-9, stir evenly, then add 0.01-10 parts of an organic silicon source, react at a reaction temperature of 25-80°C for 0.5-12h, after the reaction is completed, vacuum filter, wash the filter residue with the above-mentioned mixed solution of pure water and ethanol or methanol in turn, and repeat three times, and then dry, the drying condition is drying at 100°C to 200°C for 1h to 12h;

[0022] (2) The dried filter residue is treated in a calcining furnace at 300-800°C for 0.5-30h to remove a small amount of residual organic matter and alkaline substances, so that the hydroxyl content of silicon dioxide formed on the surface of the spherical silicon dioxide powder is more prominent;

[0023] (3) The surface of spherical silica is coated with high-purity silicon oxide formed by hydrolyzed organic silane, and a larger SiOH is formed on its surface. The pH of the aqueous solution is neutral, and then it is modified with a coupling agent to obtain a modified product. The median particle size of the spherical silica powder after surface modification is 10nm~100μm, pH=5.5~7.5, and SiOH content is 1μg / g~2000μg / g.

[0024] The alkaline substance is selected from one or more of triethylamine, ammonia water, pyridine, tetramethylethylenediamine, hexamethyldisilazane, aminopropyltriethoxysilane, methylamine, urea, dimethylamine, and aniline.

[0025] The organic silicon source is selected from at least one of methyl orthosilicate, ethyl orthosilicate, γ-(methacryloyloxy)propyltrimethoxysilane, butyltrimethoxysilane and methyltriethoxysilane.

[0026] The coupling agent is a silane coupling agent, such as Si(R 1 ) X (OR 2 ) 4-X , X can be 1, 2 or 3, R 1 is a hydrocarbon group containing an alkyl group, an epoxy group, a hydroxyl group, an amino group, a carboxyl group, a mercapto group, an isocyanate group, an ethoxy group, or a urea group, and R 2 It is methyl or ethyl.

[0027] Example 1

[0028] Take 100 parts of spherical silica powder with a median particle size of 0.5μm, add it to a mixed solution of 1000 parts of pure water and ethanol (pure water: ethanol = 50:1), then add alkaline substances to adjust the solution pH to 8, stir evenly, then add 1 part of ethyl orthosilicate, reaction temperature 45℃, reaction time 2h, filter, wash three times with the mixed solution, and dry at 120℃ for 6h. The dried material was calcined at 450℃ for 20h. The SiOH content of the spherical silica powder and the pH of the aqueous solution after treatment were detected. Then it was modified with γ-glycidyloxypropyltrimethoxysilane to obtain a modified spherical silica product, D50: 0.5μm, pH = 6.0, SiOH is 500μg / g. The corresponding cured product has a bending strength of 205Mpa.

[0029] Example 2

[0030] Take 100 parts of spherical silica powder with a median particle size of 0.5μm, add it to a mixed solution of 1000 parts of pure water and ethanol (pure water: ethanol = 100:1), then add alkaline substances to adjust the solution pH to 7.5, stir evenly, then add 1 part of ethyl orthosilicate, reaction temperature 45℃, reaction time 2h, filter, wash three times with the mixed solution, and dry at 120℃ for 6h. The dried material was calcined at 450℃ for 20h. The SiOH content of the spherical silica powder and the pH of the aqueous solution after treatment were detected. Then it was modified with γ-glycidyloxypropyltrimethoxysilane to obtain a modified spherical silica product, D50: 0.5μm, pH=5.5, SiOH is 600μg / g. The corresponding cured product has a bending strength of 192Mpa.

[0031] Example 3

[0032] Take 100 parts of spherical silica powder with a median particle size of 0.5μm, add 1000 parts of pure water and ethanol mixed solution (pure water: ethanol = 1:1), then add alkaline substances to adjust the solution pH to 8.5, stir evenly, then add 1 part of tetraethyl orthosilicate, reaction temperature 45℃, reaction time 2h, filter, wash three times with the mixed solution, and dry at 120℃ for 6h. The dried material was calcined at 450℃ for 20h. The SiOH content of the spherical silica powder and the pH of the aqueous solution after treatment were detected. Then it was modified with γ-glycidyloxypropyltrimethoxysilane to obtain a modified spherical silica product, D50: 0.5μm, pH = 5.3, SiOH is 530μg / g. The corresponding cured product has a bending strength of 181Mpa.

[0033] Example 4

[0034] Take 100 parts of spherical silica powder with a median particle size of 5μm, add it to a mixed solution of 1000 parts of pure water and ethanol (pure water: ethanol = 50:1), then add alkaline substances to adjust the solution pH to 8, stir evenly, then add 1 part of ethyl orthosilicate, reaction temperature 45℃, reaction time 2h, filter, wash three times with the mixed solution, and dry at 120℃ for 6h. The dried material was calcined at 450℃ for 20h. The SiOH content of the spherical silica powder and the pH of the aqueous solution after treatment were detected. Then it was modified with γ-glycidyloxypropyltrimethoxysilane to obtain a modified spherical silica product, D50: 5μm, pH=6.5, SiOH is 120μg / g. The corresponding cured product has a bending strength of 140Mpa.

[0035] Example 5

[0036] Take 100 parts of spherical silica powder with a median particle size of 0.5μm, add 1000 parts of a mixed solution of pure water and methanol (pure water: ethanol = 50:1), then add alkaline substances to adjust the solution pH to 7.0, stir evenly, then add 0.73 parts of methyl orthosilicate, reaction temperature 45℃, reaction time 2h, filter, wash three times with the mixed solution, and dry at 120℃ for 6h. The dried material was calcined at 450℃ for 20h. The SiOH content of the spherical silica powder and the pH of the aqueous solution after treatment were detected. Then it was modified with γ-glycidyloxypropyltrimethoxysilane to obtain a modified spherical silica product, D50: 0.5μm, pH = 6.3, SiOH is 480μg / g. The corresponding cured product has a bending strength of 198Mpa.

[0037] Example 6

[0038] Take 100 parts of spherical silica powder with a median particle size of 0.5μm, add 1000 parts of pure water and ethanol mixed solution (pure water: ethanol = 50:1), then add alkaline substances to adjust the solution pH to 8, stir evenly, then add 1 part of ethyl orthosilicate, reaction temperature 45℃, reaction time 2h, filter, wash three times with the mixed solution, and dry at 120℃ for 6h. The dried material was calcined at 450℃ for 20h. The SiOH content of the spherical silica powder and the pH of the aqueous solution after treatment were detected. Then it was modified with γ-aminopropyltriethoxysilane to obtain a modified spherical silica product, D50: 0.5μm, pH = 7.3, SiOH is 490μg / g. The corresponding cured product has a bending strength of 198Mpa.

[0039] Example 7

[0040] Take 100 parts of spherical silica powder with a median particle size of 0.5μm, add 1000 parts of pure water and ethanol mixed solution (pure water: ethanol = 50:1), then add alkaline substances to adjust the solution pH to 8, stir evenly, then add 1 part of ethyl orthosilicate, reaction temperature 45℃, reaction time 2h, filter, wash three times with the mixed solution, and dry at 120℃ for 6h. The dried material was calcined at 450℃ for 20h. The SiOH content of the spherical silica powder and the pH of the aqueous solution after treatment were detected. Then it was modified with γ-mercaptopropyltrimethoxysilane to obtain a modified spherical silica product, D50: 0.5μm, pH = 6.0, SiOH is 495μg / g. The corresponding cured product has a bending strength of 190Mpa.

[0041] Comparative Example 1

[0042] The SiOH content and the pH value of the solution of spherical silica powder with a median particle size of 0.5 μm before treatment were tested. The product D50: 0.5 μm, pH = 4.8, SiOH is 650 μg / g. The corresponding cured product bending strength is 180 MPa.

[0043] Comparative Example 2

[0044] The corresponding raw material spherical silica powder has a median particle size of 0.5 μm, and is modified using γ-glycidyloxypropyltrimethoxysilane to obtain a modified spherical silica product. Product D50: 0.5 μm, pH = 5.0, SiOH is 450 μg / g. The corresponding cured product has a bending strength of 185 Mpa.

[0045] Comparative Example 3

[0046] The corresponding raw material spherical silica powder has a median particle size of 5.0 μm, and is modified using γ-glycidyloxypropyltrimethoxysilane to obtain a modified spherical silica product. Product D50: 5 μm, pH = 5.4, SiOH is 95 μg / g. The corresponding cured product has a bending strength of 108 Mpa.

[0047] The content change of surface hydroxyl groups of the coated spherical silica powder in the present invention is quantitatively detected by acid-base titration, the pH is tested by a pH meter, and the binding force between the modified product and the resin is characterized by mechanical force. The specific test method is as follows:

[0048] (1) pH test method: 10 g of powder was added to 90 mL of pure water and 10 mL of ethanol and stirred for 30 min. The pH meter was used for testing.

[0049] (2) Hydroxyl content test: weigh mg powder and mix it with deionized water in a certain ratio, adjust the pH to 4.0, add NaOH solution to adjust the pH to 9.0, and record the volume of NaOH solution consumed V. C*(V-VB)*17.007 / m, C: NaOH concentration, mol / L; V: volume of NaOH solution consumed; VB: volume of NaOH solution consumed in blank experiment m: mass of powder g,

[0050] (3) Median particle size (D50): "D50" is the particle size at the point where 50% of the total volume of the particle size distribution calculated on a volume basis is taken as 100%, i.e., the volume basis cumulative 50% particle size. "Particle size distribution" can be calculated from the frequency distribution and cumulative volume distribution curve measured by a laser scattering particle size distribution measuring device (e.g., a laser diffraction / scattering particle size distribution measuring device, etc.). The measurement is performed by fully dispersing the powder in an aqueous medium by ultrasonic treatment or the like.

[0051] (4) 8% epoxy resin, 4% curing agent, and 88% spherical silica powder form a cured product, the flexural strength of which is tested using a universal testing machine in accordance with GB / T9341 standard.

[0052] The "particle size distribution" can be calculated from the frequency distribution and cumulative volume distribution curve measured by a laser scattering particle size distribution measuring device (eg, laser diffraction / scattering particle size distribution measuring device, etc.) The measurement is performed by sufficiently dispersing the powder in an aqueous medium by ultrasonic treatment or the like.

[0053] The processing parameters used in Examples 1-7 and Comparative Examples 1-3 and the test results obtained according to the above test method are summarized as follows (wherein, in the table, A refers to tetraethyl orthosilicate, B refers to γ-glycidyloxypropyltrimethoxysilane, C refers to γ-aminopropyltriethoxysilane, and D refers to γ-mercaptopropyltrimethoxysilane):

[0054]

[0055] It can be seen from Examples 1-7 and Comparative Examples 1-3 that the particle size has a great influence on the SiOH content of the modified spherical silica product and the corresponding curing strength. It can be seen from Example 4 and Comparative Example 7 that the larger the particle size, the smaller the SiOH content of the modified spherical silica product, and the smaller the corresponding curing strength; the corresponding curing strength reflects the interface compatibility between the inorganic product and the organic resin. The larger the corresponding curing strength, the more blurred the interface between the inorganic product and the organic resin, and the better the interface compatibility. In this regard, controlling the median particle size of the spherical silica powder as a raw material to 0.5μm is more conducive to obtaining a better modification effect. It can be seen from the above embodiments that the modified spherical silica product obtained in Example 1 has the highest SiOH content and the corresponding curing strength is better.

[0056] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing surface-modified spherical silica powder, characterized in that: The method uses spherical silicon dioxide powder produced by flame method, pH=3.0-5.5, SiOH content 1μg / g-3000μg / g, and comprises the following steps: Take 100 parts of spherical silica powder with a median particle size of 0.5 μm, add it to 1000 parts of a mixed solution of pure water and ethanol, pure water: ethanol = 50:1, then add an alkaline substance to adjust the solution pH to 8, stir evenly, then add 1 part of tetraethyl orthosilicate, the reaction temperature is 45°C, the reaction time is 2h, filter, wash three times with the mixed solution, dry at 120°C for 6h, calcine the dried material at 450°C for 20h, detect the SiOH content of the spherical silica powder and the pH of the aqueous solution after treatment, and then use γ-glycidyloxypropyltrimethoxysilane to modify it to obtain a modified spherical silica product, D50: 0.5 μm, pH = 6.0, SiOH is 500 μg / g, corresponding to a cured product flexural strength of 205 MPa, the cured product is composed of 8% epoxy resin, 4% curing agent and 88% of the modified spherical silica product.

2. The method for preparing a surface-modified spherical silica powder according to claim 1, characterized in that: The alkaline substance is selected from one or more of triethylamine, ammonia water, pyridine, tetramethylethylenediamine, hexamethyldisilazane, aminopropyltriethoxysilane, methylamine, urea, dimethylamine, and aniline.

Citation Information

Patent Citations

  • In situ modification method of electronic grade spherical packing

    CN110372913A

  • Preparation method of spherical silica micropowder for high-end copper-clad plate

    CN106335905A

  • Silicon dioxide slurry composition as well as preparation method and application thereof

    CN106700132A

  • Preparation method of spherical silicon dioxide powder filler, powder filler obtained through the method, and application thereof

    CN111886201A

  • Preparation method of high-purity silica gel

    CN112174145A